Development of Single-Nucleotide Polymorphism (SNP)-Based Species-Specific Real-Time PCR Assays for Authenticating Five Highly Priced Tuna - Meng Qu; Yanhua Jiang; Na Li; Yingying Guo; Wenjia Zhu; Na Li; Xinnan Zhao; Lin Yao; Lianzhu Wang (Foods)
Tuna are economically important as food resources in food markets. However, because tuna is often processed into steaks or fillets, the meat can be difficult to identify through morphological features. For effective fishery management and to protect the rights of consumers, it is necessary to develop a molecular method to accurately identify the species used in tuna products. Herein, we discovered five single-nucleotide polymorphism (SNP) sites via 2b-RAD sequencing and developed five SNP-based real-time polymerase chain reaction assays for the rapid identification of five highly priced tuna species. Three species-specific TaqMan systems were designed to identify albacore tuna (Thunnus alalunga), bigeye tuna (T. obesus), and southern bluefin tuna (T. maccoyii) and two cycling systems were designed to identify yellowfin tuna (T. albacares) and Atlantic bluefin tuna (T. thynnus). The systems showed good specificity and sensitivity (sensitivity of 0.0002 ng μL−1 for albacore tuna, bigeye tuna, and southern bluefin tuna and 0.002 ng μL−1 for yellowfin tuna and Atlantic bluefin tuna). Both systems were able to distinguish the target species from other species in a specific, sensitive, and accurate manner. Thus, these methods can be employed for the identification of species used in tuna products, protecting consumers and producers from economic fraud.